MicroRNAs in Cancer: A Historical Perspective on the Path from Discovery to Therapy - Orellana, Esteban A. (Cancers (Basel), 2015)
Recent progress in microRNA (miRNA) therapeutics has been strongly dependent on multiple seminal discoveries in the area of miRNA biology during the past two decades. In this review, we focus on the historical discoveries that collectively led to transitioning miRNAs into the clinic. We highlight the pivotal studies that identified the first miRNAs in Caenorhabditis elegans to the more recent reports that have fueled the quest to understand the use of miRNAs as markers for cancer diagnosis and prognosis. In addition, we provide insights as to how unraveling basic miRNA biology has provided a solid foundation for advancing miRNAs, such as miR-34a, therapeutically. We conclude with a brief examination of the current challenges that still need to be addressed to accelerate the path of miRNAs to the clinic: including delivery vehicles, miRNA- and delivery-associated toxicity, dosage, and off target effects.